PEMECAHAN MASALAH MANAJEMEN MUTU PENDIDIKAN JARINGAN SEKOLAH ISLAM TERPADU BIDANG KURIKULUM DAN KESISWAAN DI SMP IT INSAN MANDIRI KOTA SUKABUMI - Anwar, Saepul; Hidayat, Tatang; Sofwandi, Mulyawan (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2024)
The purpose of this study is to analyze the problem of quality management of integrated Islamic school network education in the field of curriculum and student affairs at SMP IT Insan Mandiri Sukabumi City. This research uses a research approach and descriptive methods. Data retrieval techniques with interviews, observations and documentation. Based on the results of the study, the implementation of integrated Islamic school network education management at SMP IT Insan Mandiri was able to improve the quality of education very well so as to give birth to a generation of students and students who have a charitable character and are able to compete with schools in Sukabumi city. In solving and solving every problem in the school, the principal as the policy maker always holds a Syuro (deliberation) every time there is a problem that occurs in the school, both related to the curriculum and student affairs of the Integrated Islamic School Network.